A Market School: Pengelolaan Pendapatan dan Laporan Keuangan Sederhana untuk Pedagang Buah - Nikensari, Sri Indah; Nurjanah , Siti; Sari Komara, Lilis (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
This community development activity aims to provide understanding of material and earnings management techniques through lectures and simple financial application practices to improve the welfare of the parent Kramatjati market fruit traders in East Jakarta. This activity is part of activities carried out jointly with the theme "School Market for the Fruit Traders in Pasar Kramatjati of East-Jakarta". The sub-material for earnings management techniques starts with brain storming about factors that affect the activities of participants. The next material is about earnins management and recording simple financial statements using the "LAMIKRO" application. This application can be downloaded from the Ministry of Cooperatives and MSEs website. This community development activity was held in the PD Pasar Jaya office hall in the Kramat Jati market environment, with lecture and paractic methods. The results of this activity include the installation of the "LAMIKRO" application for some participants to facilitate making simple financial reports that were immediately practicable.